Respon Base Care pada Mahasiswa Kesehatan: Tinjauan Literatur - Ajeng Lestari Khoirunnisa Sudika; Ati Surya Mediawati (LPPM Institut Pendidikan Nusantara Global, 2025)
Base care response encompasses the fulfillment of physiological, psychological, social, and spiritual basic needs of health science students, which influences their well-being and readiness for clinical practice. Objective: To review the factors influencing base care response among health science students. Methods: A literature review was conducted using PubMed, Google Scholar, Sage Journals, and EBSCOhost for articles published between 2015 and August 2025 in Indonesian or English, with inclusion criteria focusing on health science students and topics related to caring, basic needs, mental well-being, and self-care. Results: Students prioritized physiological aspects over emotional and spiritual needs, with 63.8% reporting moderate-to-severe stress. Discussion: The imbalance in fulfilling students’ basic needs is influenced by high academic demands and limited attention to emotional and spiritual dimensions. This condition may reduce clinical readiness and increase the risk of burnout. Conclusion: Base care response among health science students tends to be suboptimal, with a predominant focus on physiological needs. Integrating holistic caring approaches and strengthening self-care may serve as strategies to enhance students’ well-being.